2018
DOI: 10.12681/mms.14786
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and bathymetric effects on macrofouling invertebrates’ primary succession in a mediterraenan non-indigenous species hotspot area

Abstract: The present study investigates macrofouling development in the Mar Grande of Taranto (Central Mediterranean Sea), a wide confined area that has attracted considerable attention in recent years due to the establishment of numerous non-indigenous species (NIS). Different starting times of a yearly primary succession on artificial substrates were tracked so as to investigate the matching of the development pattern with contingency and/or convergence models, identifying NIS's structural role in the community endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 51 publications
8
24
0
Order By: Relevance
“…The pattern of community development observed on the bare vertical collectors utilized, containing, at the base, individuals of Sabella, agrees with previous studies on the fouling community obtained with the use of panels [75]. The macrofouling colonization investigated in the bare collector was followed until a "stable point" was reached after almost nine months; at this point, all the structures were characterized by a shallow assemblage (0-3 m), dominated by M. galloprovincialis, and a deeper assemblage (3-10 m), dominated almost exclusively by sabellid worms.…”
Section: Polychaetessupporting
confidence: 89%
See 3 more Smart Citations
“…The pattern of community development observed on the bare vertical collectors utilized, containing, at the base, individuals of Sabella, agrees with previous studies on the fouling community obtained with the use of panels [75]. The macrofouling colonization investigated in the bare collector was followed until a "stable point" was reached after almost nine months; at this point, all the structures were characterized by a shallow assemblage (0-3 m), dominated by M. galloprovincialis, and a deeper assemblage (3-10 m), dominated almost exclusively by sabellid worms.…”
Section: Polychaetessupporting
confidence: 89%
“…The temperature shows seasonal variations typical of the coastal Ionian regions with an average annual value of about 18 • C, while the salinity is about 38% and is almost uniform over the year. The area is affected by intense Mytilus galloprovincialis farming, a species that finds, in the area, optimal conditions to dominate the final stage of the shallow local fouling communities, sometimes competing with solitary ascidians as well as with sabellid polychaetes [73][74][75].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted by means of artificial panels in this biotope showed a higher fouling diversity linked to the abundance of AS. In particular, two congener polychaete sabellids, Branchiomma luctuosum and B. boholensis , together with the colonial ascidian Polyandrocarpa zorritensis , hamper the dominance of M. galloprovincialis at the surface of the system, so fostering a more diverse benthic assemblage (Lezzi & Giangrande, 2018). Our monitoring studies in the area have been going on for 30 years (Giangrande, Licciano, et al, 2014).…”
Section: The Other Side Of Biological Invasionsmentioning
confidence: 99%